Analisis Pengaruh Social Media Marketing Campaign Yogurt X Melalui Instagram Terhadap Keputusan Pembelian - Ricky Aditya (Lembaga Intelektual Muda (LIM) Maluku, 2022)
This study aims to determine the magnitude of the influence of Social Media Marketing during campaigns through Instagram on Yogurt X product purchase decisions. The study population was Instagram followers of Yogurt X. Large samples to be taken in this study can be determined through the slovin formula. Researchers used an error tolerance (e) of 10 percent and a population of 29,300 followers of Instagram Yogurt X. Based on the results of these calculations, it can be seen that the sample in this study amounted to 100 people. Sampling in this study was carried out by Nonprobability Sampling. The sampling technique in this study used incidental sampling. Incidental sampling is a sampling technique based on chance, i.e. anyone who incidentally meets the researcher can be used as a sample. The results of the Partial Test (Test t) show that Context (X1), Collaboration (X3) and, Connection (X4) have a significant effect on Yogurt X Purchasing Decisions, while Communication does not have a significant effect on Yogurt X Purchasing Decisions. The magnitude of the influence of Sub Variability (Context, Communication, Collaboration, Connection) on sequential Purchasing Decisions is Context 18.8 percent, Communication 2.94 percent, Collaboration 22.21 percent, Connection 17.47 percent. The results of the Simultaneous Test (Test F) show that Social Media Marketing Yogurt X through Instagram social media affects Purchase Decisions. The magnitude of the influence of the independent variable on the dependent variable was 61.4 percent, while the remaining 38.6 percent was influenced by other variables that were not studied